Cerebral Venous Thrombosis as an Initial Presentation of Ulcerative Colitis - Hiroshi Yamazaki; Akinori Sasaki; Eriko Yamaguchi; Kana Sawada; Risa Okamoto; Kuniyasu Saigusa; Yasuaki Motomura (Case Reports in Gastrointestinal Medicine)
Cerebral venous thrombosis (CVT) is a rare complication of ulcerative colitis (UC) that is potentially fatal once it occurs. This report describes a case of CVT that led to a diagnosis of UC. A 48-year-old woman was diagnosed with CVT due to paresthesia and weakness and was hospitalized for treatment. She developed bloody diarrhea on admission and was further diagnosed with UC based on endoscopic and pathologic findings. Treatment of UC with steroids and sulfasalazine was administered immediately. Her condition improved significantly within several days following treatment. After discharge, the patient experienced no recurrence of either CVT or UC flare-up over the last five years. This report describes CVT as an initial presentation of UC. This is also the first report of a long-term follow-up following successful treatment of CVT with concomitant UC.